PERBEDAAN PENGARUH MENYUSUI SELAMA ENAM MINGGU POSTPARTUM TERHADAP PERUBAHAN BOBOT BADAN IBU - Yusniarita, Yusniarita (JURNAL MEDIA KESEHATAN, 2013)
The body weight will return weight of body after delivering birth. One of way that is most safe to reduce body weight after delivering birth is suckle, sufficiency of intake energy, consumption of fibrous food and mother routine activity after delivering birth. Difference Lactation during six week post partum to change of mother body weight. Research planning applied is cohort prospective with number of samples 70 breast-feeding motherses fulfilling criterion inklusi. Sampling with technique purposive sampling. Data is analysed in univariate, bivariate with T-Test and Multivariate with linear regression. After analysed, there were no difference of signifikan average of the body weight between mothers having low activity with mother doing high activity with value p > 0,05. There is difference of average of the body weight mother at week ke-6 with frequency suckles > 6 times/day with breast-feeding mothers < 6 times/day. Average Of the body weight ( 57,4667 g) at suckling mother > 6 times/day during 6 week compared to breast-feeding mothers < 6 times/day ( 53,7791 g). Dominance factor is intake energy and intake fibre both having difference that signifikan with value p < 0,05.Mother suckling during 6 week with frequency suckles > 6 times/day experiences improvement of body weight compared to mother suckling with frequency < 6 times/day.